An Empirical Study of Batik Talunombo Wonosobo: Analyzing the Impact of Brand Image and Digital Marketing on Consumer Purchase Interest - M. Trihudiyatmanto (UP2MF Fakultas Ekonomi dan Bisnis, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2025)
Purpose - This study aims to demonstrate the influence of brand image and digital marketing on consumer purchase intention for Batik Talunombo Wonosobo. This study was conducted with consumers of Batik Talunombo Wonosobo. Method - The data used were primary data obtained directly from respondents. This study employed a quantitative approach. The sampling method used incidental sampling. Therefore, the sample size for this study was 105 respondents, who were consumers of Batik Talunombo Wonosobo. The data were analyzed using multiple linear regression equations with SPSS version 25. Findings - The results of the study indicate that brand image has a positive effect on consumer purchase intention, as evidenced by a calculated t-value of 2.345 > t-table 1.98282 with a significance level of 0.021 < α 0.05. Digital marketing has a positive effect on consumer purchase intention, as evidenced by a calculated t-value of 3.241 > t-table 1.98282 with a significance level of 0.002 < α 0.05. Implications – This will enable managers and business owners to understand the psychological factors that consumers need to improve to maintain their presence amidst digital competition.